QUALITY OF THE ENVIRONMENT AND MEDICAL-GEOGRAPHICAL SITUATION IN THE SUMY REGION - Kornus, Anatolii; Kornus, Olesya; Shyschuk, Volodymyr (Human Geography Journal, 2016)
Today is still insufficiently developed the methods of associative analysis of the medical, ecological and demographic parameters that would make it possible to determine the nature and extent of the influence of environmental factors on the population health. In the integrated form, the quality of drinking water is the most important factor, which closely correlated with the prevalence of diseases among the population of Sumy region. The influence of the ecological state of the air, including the gamma-background level, chemical and radioactive contamination of soils and crop production are also important, although less markedly.